Cytotoxic Potential of Extract Methanol and Fraction of African Leaf (Vernonia amygdalina Del.) on B16F10 Cell Line in Melanoma Cancer - Sahwani Risqina Lubis; Poppy Anjelisa Zaitun Hasibuan; Denny Satria (Jurnal FARMASIMED (JFM), 2026)
Melanoma is a highly aggressive malignancy derived from melanocytes and is considered the most severe form of skin cancer. Natural products have increasingly attracted attention as potential sources for the discovery of novel anticancer agents. The purpose of this study is to assess the cytotoxic activity of Vernonia amygdalina Delile leaf methanol extract and chloroform fraction against B16F10 melanoma cells. Vernonia amygalina Del. Leaves extracted using reflux method and liquid-liquid fractionation. Identification of the contained compounds were identified using thin layer chromatography. B16F10 cells were cultured under standard conditions and treated with various concentrations of the chloroform fraction and methanol extract of Vernonia amygdalina Delile leaves and the cytotoxicity assay was performed using the MTT method to determine cell viability and IC₅₀ values. The analysis revealed IC₅₀ values of chloroform fraction (81.80±4.18) and followed by n-hexane fraction (187.33±12.48), etil acetate fraction (204.35±8.39), methanol extract (344.37±25.12) and residual fraction (4032.38±921.22). All fraction and the methanol extract demonstrated dose-dependent cytotoxicity, with the chloroform fraction exhibiting a more pronounced inhibitory effect. These results suggest that Vernonia amygdalina leaves contain bioactive constituents with significant anticancer potential against melanoma. Future studies should focus to the isolation of active compounds and comprehensive in vivo validation to strengthen the therapeutic prospects.